EFFICIENT IMPROVEMENTS OF HERPEX SIMPLEX LABIALIS TREATMENT USING DIODE LASER AND “TEBODONT” GEL - М.А. Gorai; L.F. Kurdysh; O.I. Popova; О.І. Kutelmakh (Український стоматологічний альманах)
The introduction of laser systems into the dental practice takes an important place in the development of methods for accelerated and effective treatment of viral diseases. As a matter of fact, laser radiation blocks the inflammatory process, suppresses the pathogenicity of the virus, improves the processes of microcirculation. The use of tea tree oil-based preparations promotes regeneration and restoration of the tunica mucosa of mouth.